Visitor Growth Strategies: Evaluating the Effectiveness of Tourism Marketing at Kebun Raya Mangrove Surabaya - Galuh Ajeng Ayuningtiyas; Muhammad Khairul Anwar; Dian Ferriswara; Liling Listyawati; Damajanti Sri Lestari (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
Kebun Raya Mangrove (KRM) Surabaya is the first thematic botanical garden in Indonesia that focuses specifically on the mangrove ecosystem. It serves multiple functions, including conservation, education, research, and recreation. With its ecological uniqueness, KRM has strong potential to develop into a prominent ecotourism destination. However, post-pandemic conditions have seen a significant decline in visitor numbers, indicating the urgent need for more effective and targeted marketing strategies. This study aims to identify and evaluate marketing strategies that can enhance tourist interest and increase visitation to KRM Surabaya. The research adopts a descriptive method with a qualitative approach by collecting both primary data (through observations and interviews) and secondary data, which are then analyzed thematically. The findings indicate that KRM is currently facing several critical challenges, including limited accessibility, inadequate digital promotion, and environmental maintenance issues. Existing marketing efforts—such as affordable ticket pricing, minimal promotion via the official social media accounts of the Food Security and Agriculture Service, and limited collaboration with local SMEs—have not successfully expanded KRM’s market reach or visibility. To address these gaps, the study recommends a comprehensive marketing strategy that includes the optimization of digital marketing through official KRM-managed social media channels, strategic partnerships with ecotourism influencers, the organization of thematic events (e.g., mangrove festivals), and the innovation of mangrove-based products that can boost local identity and visitor engagement. By implementing these strategies, KRM is expected to strengthen its destination branding, attract a broader audience, and establish itself as a leading model for sustainable tourism in Surabaya and beyond.